La desigualdad de género y pobreza en América Latina, período 2010-2019 - Roxana Elizabeth, Moreno Gualli (2021)
ABSTRACT The objective of this research is to determine the incidence of gender inequality in poverty in Latin American countries during the period 2010-2019. For which it is important to analyze that the construction of a participatory state requires equity as a condition of the social structure. Over time, based on the need to combat social problems that affect different countries of the world, there are organizations and studies that show that the study of poverty is not only framed in the economic sphere but has a multidimensional vision. Thus, the gender approach used to assess poverty allows us to understand some of the processes, characteristics and phenomena that explain why certain groups, according to their gender, are more likely to be poor. It was assessed using the vector autoregressive model (VAR). The cointegration existing between the variables is also checked using the Engle-Granger, augmented DickeyFuller, Bartlet and Q de Portmanteau methodology. In addition to estimating the causality between the variables through causality in the sense of Granger. The results obtained indicate that there is a direct relationship between gender inequality and poverty; In other words, an increase in the gender inequality index affects the increase in the poverty gap. Keywords: inequality, gender, poverty, discrimination Reviewed by: Lic. Marlene de la Caridad Mena Viamonte ENGLISH PROFESSOR C.C. 1758391393